Cognitive functioning and soccer heading: one-year longitudinal assessment among professional players - Giovanni Batista Palma; Mariana Drummond Martins Lima; Ana Carolina Oliveira Rodrigues; Clarisse Vasconcelos Friedlaender; Celso Furtado de Azevedo Filho; Rodrigo Campos Pace Lasmar; Paulo Caramelli (Arquivos de Neuro-Psiquiatria)
Background Soccer is the most popular sport worldwide, and the only one in which players purposely and repetitively use their head to hit the ball. In recent years, more attention has been given to subconcussive impacts, which are characterized by a cranial impact that does not result in known or diagnosed concussion on clinical grounds.